Ultrasound-Guided Cannulation of the Brachiocephalic Vein in Neonates and Preterm Infants: A Prospective Observational Study - Oulego-Erroz, Ignacio; Alonso-Quintela, Paula; Terroba-Seara, Sandra; Jiménez-González, Aquilina; Rodríguez-Blanco, Silvia; Vázquez-Martínez, José Luis (American Journal of Perinatology, 2018)
Introduction Percutaneous central venous catheter (CVC) insertion is a challenging procedure in neonates, especially in preterm infants.Objective This study aims to describe the technical success and safety profile of ultrasound (US)-guided brachiocephalic vein (BCV) cannulation in neonates.Methods Prospective observational study. Neonates admitted to the neonatal intensive care unit (NICU) in whom US-guided cannulation of the BCV was attempted were eligible. Outcomes included first attempt success rate, the overall success rate, the number of attempts, the cannulation time, immediate mechanical complications, catheter indwelling days, and late complications.Results A total of 40 procedures in 37 patients were included. Median weight and age at the time of cannulation were 1.85 kg (0.76–4.8) and 13 days (3–31), respectively. First attempt and overall success rates were 29 (72.5%) and 38 (95%), respectively. No major complications were observed. Catheter-associated infection rate was 2.4/1,000 catheter days. There were no difference in outcomes between low weight preterm infants (<1.5 kg) and the rest of the cohort. There was no linear relationship between weight at time of insertion and the number of puncture attempts (r = 0.250; p = 0.154) or cannulation time (r = 0.257; p = 0.142).Conclusion US-guided cannulation of the BCV may be considered in acutely ill neonates, including small preterm infants, who need a large bore CVC.
Keywords: ultrasound; central venous catheter; neonate; preterm; brachiocephalic vein; neonatal intensive care unit